Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
The following values have no corresponding Zotero field: periodical: Handbook Of Operations Research In Natural Resources electronic-resource-num: 10.1007/978-0-387-71815-6
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model